Analisis Sentimen Terhadap Kontroversi Putusan MK Mengenai Usia Capres-Cawapres Menggunakan Multi-Layer Perceptron Dengan Teknik SMOTE - Sasmita, Sasmita; Jariah S.Intam, Rezki Nurul; Surianto, Dewi Fatmarani; B, Muhammad Fajar (Faktor Exacta, 2024)
In October 2023, the Constitutional Court's decision on age limit requirements for presidential and vice-presidential candidates stirred controversy, perceived as favoring a specific vice-presidential candidate. Public reactions flooded social media platforms, particularly on Najwa Shihab's YouTube channel, where sentiment analysis was conducted on 505 comments under the video titled "Putusan MK: Publik memang Seharusnya Marah" (Constitutional Court Decision: The Public Should Indeed Be Angry). The comments were categorized into three sentiment classes: 425 negative, 42 neutral, and 38 positive. The study employed Multi-Layer Perceptron (MLP) models tested on both imbalanced and balanced data using the SMOTE oversampling technique. Two feature extraction methods, TF-IDF weighting and countvectorizer, were applied. Results showed that the combination of TF-IDF with balanced data yielded the most effective classification model, boasting a remarkable accuracy, precision, recall, and F1-score, each at 99%.